Modification of nylon-6 fibres by radiation-induced graft polymerisation of vinylbenzyl chloride. (April 2015) - Ting, T.M.; Nasef, Mohamed Mahmoud; Hashim, Kamaruddin
Abstract: Modification of nylon-6 fibres by radiation-induced graft copolymerisation (RIGP) of vinylbenzyl chloride (VBC) using the preirradiation method was investigated. A number of grafting parameters such as type of solvent, total dose, monomer concentrations, reaction temperature and reaction time were studied to obtain desired degree of grafting (DG). The DG was found to be a function of reaction parameters and achieved a maximum value of 130 wt% at 20 vol% VBC concentration in methanol, 300 kGy dose, 30 °C temperature and 3 h reaction time. Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and X-ray diffraction (XRD) were employed to evaluate the chemical, morphological and structural changes that occurred in the grafted fibres, respectively. Thermogravimetric analysis (TGA) was also applied to determine the thermal stability, whereas differential scanning calorimeter (DSC) and universal mechanical tester were used to analyse respective thermal and mechanical properties of the grafted fibres. The results of these analyses provide strong evidence for successful grafting of VBC onto nylon-6, and the variation in the properties of the grafted fibres depends on DG. Highlights: Modification of nylon-6 fibres by radiation induced grafting of VBC in methanol. Establishment of relations between DG and reaction parameters. Evidence of VBC grafting was provided by FTIR, SEM, XRD, DSC and TGA. The properties of VBC-grafted nylon-6 fibres depend on DG. Amendable VBC-grafted nylon-6 fibres retain favourable properties.